Design of Boosted Multilevel DC-DC Converter for Solar Photovoltaic System - R. Uthirasamy; V. Kumar Chinnaiyan; S. Vishnukumar; Alagar Karthick; V. Mohanavel; Umashankar Subramaniam; M. Muhibbullah (International Journal of Photoenergy)
Integration of renewable energy sources to the grid-connected system has influenced scholarly research in recent times to evolve solutions for power electronic conversion. Particularly, solar photovoltaic (SPV), being a resource available throughout the year, demands needful research to meet the demand for industrial applications. To facilitate SPV, multilevel inverters (MLIs) and cascaded H-bridge inverters (CHBIs) are proposed in the literature to meet the power requirement. However, these circuits suffer from efficiency loss, economic aspects of DC sources usage, and switching losses. Hence, in this research, a new power converter topology is projected to improve the overall efficiency of SPV systems. Further, a three-level approach involving (i) SPV Panel-Temperature Reduction (SPV-PTR) Setup, (ii) Boost Multilevel Direct Current Link Converter (BMLDCLC), and (iii) use of effective snubber modules (SM) are effectively handled to promote the industry readiness of the proposed system. From a detailed system investigation, it is seen that the proposed arrangement has minimized the power loss to ensure better quality in output. Furthermore, the software-based results and hardware setup of the planned comprehensive converter have shown promising results in terms of (i) reduced voltage stress, (ii) reduced total harmonic distortion (THD) without filter component, and (iii) reduced power loss. It is observed that the experimental setup has reported a 12.9% of excess heat removal, 5% decrease in harmonics, and 33% switch reduction than the existing MLI schemes. In addition, the proposed setup is suggested to apply for industrial purposes indicate its efficacy to be a solution in real time.